NURSE’S ROLE IN POST-OPERATIVE THIRST MANAGEMENT: A SCOPING REVIEW PROTOCOL - Martins, Andreia; Topa, Paula; dos Santos, Eugénia; Moreira, Helena; Carvalho, Ana; Alves, Sofia; Castro, Carla; Ramos, Tiago (Health and Society, 2023)
Background: Thirst is an uncomfortable and extremely prevalent symptom in the post-operative period, yet it is often undervalued. It is important for the healthcare team to assess the patient and develop strategies to manage thirst more effectively in the post-operative period. Objective: To map the scientific evidence on nurse interventions in post-operative thirst management. Review method: Scoping review methodology proposed by the Joanna Briggs Institute. The process of analysing, extracting and synthesising the data will be carried out by independent reviewers. This protocol is registered on the Open Science Framework platform (DOI: 10.17605/OSF.IO/BY73C). Presentation and interpretation of results: The mapping of Nursing Interventions/Headquarters Management Strategies in the post-operative period will enable the creation of action protocols for the care of surgical patients in the post-operative period. Conclusion: The identification of post-operative thirst management strategies will improve the quality of nursing care provided to surgical patients.